NEOTECTONIC DEFORMATION OF EASTERN PYLIA ( SW PELOPONNESE , GREECE ) - Ladas, I.; Mariolakos, I.; Fountoulis, I. (Bulletin of the Geological Society of Greece, 2004)
The present paper aims to the understanding of the effect of the morphotectonic factors on the formation of the morphoneotectonic macrostructures that comprise the eastern part of Pylia Peninsula (SW Péloponnèse). As the broader area of Pylia is one of the tectonically and seismically most active areas of the Hellenic arc, due to the fact that it is very near to the Hellenic trench (approximatly 50Km), the peninsula of Pylia is strongly considered to be a suitable area to study the neotectonic deformation at the Eastern Mediterranean region.